Factors influencing EFL students’ motivation to communicate in flipped learning: a mixed methods case study of an English debate course in China - Lixia, Cao; Ismail, Lilliati; Noordin, Nooreen (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the impact of flipped learning on motivation to communicate among EFL college students enrolled in an English debate course in China, framed by Achievement Goal Theory and Constructivist Learning Theory. A sample of 64 second-year English majors from a university in Sichuan was divided into experimental and control groups. Over 16 weeks, the experimental group experienced flipped learning, while the control group engaged in conventional blended learning. Data were gathered through pre- and post-treatment motivation questionnaires and a focus group interview. An Explanatory Sequential Mixed Methods Design was employed, combining quantitative and qualitative analyses. Results revealed that the experimental group showed significant improvements in General Motivation (p = .005), Performance Goals (p = .004), and Social Goals (p = .026), although no significant change was observed in Mastery Goals (p = .116). Notably, while Social Goals slightly improved in the experimental group, they declined in the control group. Qualitative analysis uncovered three main themes: Student Engagement, Collaboration and Interaction, and BP Debate Exercise. These findings suggest that flipped learning enhances motivation more effectively than conventional blended learning, providing valuable insights for future EFL education research in China.